The Contextual Meaning of Japanese Setsuzokushi - Septrian Adhi Saputro; Idah Hamidah; Dian Bayu Firmansyah (Universitas Dian Nuswantoro, 2021)
This study describes the contextual meaning of the noni and kuseni conjunctions in the drama dialogue Dragon Zakura. This study uses a qualitative paradigm with syntactic and semantic research approaches. The research data source is a Japanese drama entitled Dragon Zakura with data in conversational sentences. There is noni or kuseni conjunction, which is collected through the ‘simak-catat’ technique. Through Makino (1994) and Chandra (2009)'s concept of noni and kuseni, data are interpreted using contextual meaning. The results of this study indicate that the noni and kuseni conjunctions are included in gyakusetsu no setsuzokujoshi. The two conjunctions, namely noni and kuseni, although they have similarities in stating the contradiction between two things, namely between what the speaker thinks/suspected/should have, and the facts that occur, noni is more broad and objective. Noni can express negative feelings, such as disappointment, criticism, and frustration, but can also express neutral or positive emotions, such as admiration. Meanwhile, kuseni are only used to describe the speaker's negative feelings, such as criticism, annoyance, and disappointment